Prodromal interventions for schizophrenia vulnerability: the risks of being “at risk” - Corcoran, Cheryl (2005)
Given the morbidity and difficulty of treating psychotic disorders, including schizophrenia, there has been a move toward identifying and treating adolescents and young adults who appear to be clinically at risk or “prodromal” to psychosis. The field now has greater specificity in identification, with rates of 40–50% conversion to frank psychosis within 1–2 years. There is further evidence that medications and other treatments may have some efficacy for “prodromal” patients, though with variable side effects. However, controversy remains about some of the inherent risks in prodromal research, such as medication exposure and stigma among false-positives. In this paper, we add to this discussion through an analysis of ethics in prodromal research from the more established field of predictive genetic testing. Issues are raised about the effects of information on patients, families, and institutions, as well as future insurability, the limits of confidentiality (as it relies on discretion of patients and families), the autonomy of minors with psychiatric symptoms, and even the risks for the true-positive patient.